An ecological model of mediators of change in Couple Relationship Education. (February 2017) - Halford, W Kim; Pepping, Christopher A
Highlights: Relationship Education (RE) improves satisfaction for particular couples. The mediators of RE are not established. Mediator of RE are moderated by context, life events and partner characteristics. Mediation models need to include multi-factorial risk indices. Abstract : Couple Relationship Education (RE) seeks to enrich couples' relationships, and assist them to manage stressful life events [1 ]. In the current paper we present an ecological model of couple relationships intended to guide the practice of RE, analyze the mediators of RE effects, and suggest future research needs to assess moderators and mediators of RE effects in order to enhance the impact of RE.